The procedures of obtaining building licenses for high-rise building / Adlina Syazana Azman - Azman, Adlina Syazana (Universiti Teknologi Mara, Perak, 2018)
This project consist of 5 chapter which overall will conclude to a conclusion related to the company management or the works executed at the case study. In chapter 1, the details of the company will be reviewed for example the background of the company, the list of major occupants and the facilities and building services provided in the building. In Chapter 2, the general information related to the topic selected must be discussed based on literature review such as through books, internet, or an interview. The definition, the advantages and the disadvantages must be explained so that people would get a little knowledge related to the topic selected. Moving on to the next chapter which is Chapter 3; Case Study, the method statement or the installation works must be presented clearly based on the case study selected. All of the information should be gathered by referring to primary sources such as through working experience or practice on site. Last but not least, in the final chapter students need to identify the problems in chapter 1 to chapter 3 and recommend ways to solve the problems.